The Legal Dimension of Indigenous Communities Role in Climate Change Mitigation and Adaptation - Irwan Kurniawan; Etis Cahyaning Putri (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
Indigenous peoples in Indonesia have a system of values and laws that have been attached to them for a long time. The existence of a system of values and laws that have bound indigenous peoples makes them a strong and empowered society. However, the existence of customary law communities is often placed in a position that is considered an obstacle to progress, even though the rights of customary law communities have been enshrined in the Indonesian constitution. As a group that still preserves the values that have always existed, climate change is also a challenge for indigenous peoples. This study focuses on the gap between constitutional norms and the practice of national climate policy and the state's role in responding to climate change. This research uses normative and socio-legal methods using conceptual, statutory, case and sociological approaches that provide space to read the structural and political dynamics behind the neglect of the role of indigenous peoples in climate policy. The absence of indigenous peoples in climate policy architecture reflects the state's failure to integrate the principles of ecological justice into the legal system and environmental governance.